Recent advancements in two-dimensional transition metal dichalcogenide materials towards hydrogen-evolution electrocatalysis - Jianmin Yu; Gongao Peng; Lishan Peng; Qingjun Chen; Chenliang Su; Lu Shang; Tierui Zhang (Green Energy & Environment)
Hydrogen evolution reaction (HER) plays a crucial role in developing clean and renewable hydrogen energy technologies. However, conventional HER catalysts rely on expensive and scarce noble metals, which is a significant challenge for practical application. Recently, two-dimensional transition metal dichalcogenides (2D-TMDs) have emerged as attractive and cost-effective alternatives for efficient electrocatalysis in the HER. Substantial efforts have been dedicated to advancing the synthesis and application of 2D-TMDs. This review highlights the design and synthesis of high-performance 2D-TMDs-based HER electrocatalysts by combining theoretical calculations with experimental methods. Subsequently, recent advances in synthesizing different types of 2D TMDs with enhanced HER activity are summarized. Finally, the conclusion and perspectives of the 2D TMDs-based HER electrocatalysts are discussed. We expect that this review will provide new insights into the design and development of highly efficient 2D TMDs-based HER electrocatalysts for industrial applications.